An application of conjoint analysis to explore user perceptions on management information systems: A case study. Issue 1 (14th January 2014) - Lee, EunSu; Rhim, Hosun
Abstract : Purpose: – This paper aims to investigate user preferences for the information systems in order to achieve user satisfaction by using conjoint analysis. Design/methodology/approach: – Conjoint analysis is applied for the measurement of user preferences on information systems by seven properties and three levels for each property. To apply the approach, two surveys were designed: the first survey investigates the main properties affecting the end-users' satisfaction for using the current information systems based upon literature review and expert interview in Phase I. The second survey weighed the preferences by the virtual profiles of the information systems, which represent the ideal systems. Findings: – The results show that speed-related properties are critical to achieve the end-user satisfaction. The next important property group is related to the access control and system integration between various business modules. From the measurements, the best system file should be constructed with the highly weighed levels of the key attributes. Research limitations/implications: – The virtual profiles are complex for respondents to understand the attributes and the compounds of the virtual products. Moreover, the respondents were overwhelmed by the number of virtual profiles. The attributes were required to enable communication between researchers and respondents. Practical implications: – Information system designers can achieve user satisfaction by combining the highest utility levels of all attributes. Nonetheless, the trade-offs between attributes and their levels should be considered in order to apply the results to the business, depending on the system environments and business practices, by updating the importance of the determinants regularly. Originality/value: – This study applied the conjoint analysis to information management systems in order to design and maintain user satisfaction for the targeted company. This paper will provide alternative ways for the system engineers and developers of the case company by considering the critical attributes, which will affect both user performance and satisfaction.